A Report on An Online Knowledge Transfer System for Troubleshooting based on Remote Cooperative Work - Shimakawa, Haruna; Yamada, Ryota; Moriya, Toshihiro; Inui, Kazushi (Journal of Japan Society for Fuzzy Theory and Intelligent Informatics, 2008)
In this paper, we explain about SOBA Framework, a software platform for creating remote communication tools, and a knowledge management system. Then, we explain the mechanism of knowledge transfer, and validate the evidence to obtain how much effect is achieved. In the mother factory system, to provide technical assistance for each subsidiary factory in foreign country, a factory in home country will be assigned as a mother factory. Then, the mother factory will be in charge for providing technical assistance and dispatch engineers for its subsidiary factory. This method is widely employed by companies in automotive industry. However, if there is a trouble and the engineers in charge at the subsidiary factory can not solve it, it will be necessary to ask the experts in the mother factory for help by visiting the subsidiary factory. This needs an enormous cost. Moreover, the trouble is left until the expert arrives at the subsidiary factory. In addition, it leads to the decrease in productivity by restraining the experts for a long time. Then, we developed an online knowledge transfer system. This system is based on SOBA Framework, a software platform for creating remote communication tools, and a knowledge management system.